Dental workpiece and method for manufacturing same

By using alumina slurry with high erosion rate and grain size in dental treatment, high-strength zirconia sintered bodies are prepared, which solves the problem of difficult mechanical processing of zirconia sintered bodies and achieves excellent mechanical processing of sintered bodies Sexual and economical.

CN119301089APending Publication Date: 2025-01-10KURARAY NORITAKE DENTAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380044113.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-01
Filing Date
2023-06-01
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing zirconia sintered bodies are difficult to process in the sintered state, resulting in extended dental treatment time, rapid tool consumption, low productivity and economicality.

Method used

By using spherical alumina slurry with an average particle size of 3.0 μm in the particle spray test, the erosion rate reached 6.5 μm/g or the erosion rate × average grain size value was 15 μm2/g or more, the erosion rate was 15 μm2/g, and a high-two was prepared. The dentistry to be processed body with shaft bending strength achieves excellent mechanical machining properties of the sintered body.

Benefits of technology

It realizes rapid and economical mechanical processing in the sintered body state, reduces tool consumption, improves the productivity and economicality of dental treatment, and shortens treatment time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301089A_ABST
    Figure CN119301089A_ABST
Patent Text Reader

Abstract

Provided is a dental workpiece which has strength suitable for dental use and has excellent machinability in a sintered state. The present invention pertains to a dental workpiece in which the erosion rate is 8.0 [mu] m / g or more or the value of erosion rate ([mu] m / g) * average grain size ([mu] m) is 15 [mu] m < 2 > / g or more and the biaxial bending strength measured in accordance with ISO 6872: 2015 is 300 MPa or more when a spherical alumina slurry having an average grain diameter of 3.0 [mu] m is projected in a fine particle spray test.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a dental workpiece and a method for producing the same. More specifically, the present invention relates to a dental workpiece having excellent strength and light transmittance and excellent machinability in a sintered body state and a method for producing the same. Background Art

[0002] Ceramics made of metal oxides are widely used in industry. Among them, sintered zirconium oxide is used for dental materials such as dental prostheses due to its high strength and aesthetic properties.

[0003] Zirconia sintered bodies have excellent strength, so when used for dental materials such as prostheses, they are almost free from breakage and other problems. In addition, zirconia sintered bodies have high light transmittance and are not easily stained in the oral cavity, so they are also excellent in aesthetics. On the other hand, after being made into a sintered body in a completely sintered state, it has high hardness and therefore cannot be processed using a dental processing machine. For example, when a cubic zirconia sintered body is machined to obtain a zirconia sintered body having a shape that matches the shape of a patient's teeth, the consumption of metal processing tools is very large, and it takes a long time to manufacture just one dental prosthesis.

[0004] In view of this situation, when using a zirconia sintered body for dental material applications, a pre-sintered body in a semi-sintered state that is easy to process is generally processed into the shape of a desired dental prosthesis, rather than a fully sintered body, and then further sintered to produce a sintered body processed into the shape of a target dental prosthesis. Thereafter, when the sintered body having the shape of a dental prosthesis is installed in the patient's mouth at a dental hospital, the sintered body is subjected to a slight adjustment process to ensure that it fits the patient without discomfort.

[0005] In recent years, when processing a calcined body into a desired shape of a dental prosthesis, machining based on a CAD / CAM system is used. The CAD / CAM system can obtain a shape that matches the teeth of the patient's treatment site, and a CAD / CAM system is often used to process the calcined body (mill blank).

[0006] As described above, when zirconia sintered bodies are used for dental material applications, due to the unique problems of zirconia in sintering, large-scale mechanical processing is avoided after the sintered bodies are made, and the processing of the sintered bodies is limited to the level of fine-tuning when they are installed in the patient's mouth in a dental hospital. In other words, the response to the use of dental materials is carried out in accordance with the staged physical property changes caused by the sintering of zirconia.

[0007] Furthermore, in dental treatment, in consideration of the unique circumstances caused by the physical properties of the above-mentioned zirconia sintered body, treatment is usually carried out through the following multiple steps: a step of obtaining information on the shape of the patient's oral cavity, such as dentition information; a step of machining the calcined body (mill blank) into the shape of a desired dental prosthesis using a CAD / CAM system based on the acquired information; a step of sintering the calcined body having the shape of the desired dental prosthesis to obtain a sintered body; and a step of performing minute adjustments to the sintered body in order to achieve matching without discomfort when installing it in the patient's oral cavity in a dental hospital.

[0008] As described above, in dental treatment using a dental prosthesis made of sintered zirconium oxide, it is difficult to complete all the above steps in one visit to the hospital. Therefore, even if it is just to treat one tooth, it is necessary to visit the dental hospital several times, and the treatment period from the start to the end of the treatment often takes more than one month.

[0009] On the other hand, patients have an increasing demand every year to reduce the number of visits to the hospital and complete treatment in a short period of time in order to shorten the time until new artificial teeth are installed after treatment and reduce the burden of visiting the hospital.

[0010] Assuming that large-scale machining can be performed on the zirconia sintered body, there is no need to temporarily perform machining on the pre-burned body and then manufacture the sintered body by sintering. After obtaining information on the shape of the patient's oral cavity, the unprocessed sintered body can be machined into the shape of the desired dental prosthesis based on the information and using a CAD / CAM system, and then installed in the patient's mouth and fine-tuned, and dental treatment can be completed within one day.

[0011] In addition, when using dental prostheses, dental treatment that can be completed within one day can also be achieved when using materials other than zirconia such as lithium disilicate glass ceramics and feldspar glass ceramics. However, in the case of zirconia sintered bodies, there are unique circumstances caused by the physical properties of zirconia sintered bodies, which makes it difficult to achieve.

[0012] As described above, the demand for zirconium oxide is high from the perspective of strength and aesthetics. Therefore, as the demand for shortening the treatment period increases, a zirconium oxide sintered body has been proposed that has excellent machinability in the sintered body state and can be processed from a prismatic or disc-shaped mill blank into the shape of a desired dental prosthesis (for example, Patent Documents 1 and 2).

[0013] For example, Patent document 1 discloses a machinable zirconia and a method for manufacturing the same, wherein the machinable zirconia is a sintered body formed in a manner comprising a tetragonal zirconia composite powder and a TiO2 nanopowder, wherein the tetragonal zirconia composite powder comprises 79.8 to 92 mol% of ZrO2 and 4.5 to 10.2 mol% of Y2O3, and comprises 3.5 to 7.5 mol% of Nb2O5 or 5.5 to 10.0 mol% of Ta2O5, and the mass ratio of the TiO2 nanopowder to the aforementioned zirconia composite powder exceeds 0 mass% and is less than 2.5 mass%.

[0014] In addition, Patent Document 2 discloses a zirconium oxide composition and a method for manufacturing the same, wherein the zirconium oxide composition contains 78 to 95 mol% of ZrO2, 2.5 to 10 mol% of Y2O3, and 2 to 8 mol% of Nb2O5 and / or 3 to 10 mol% of Ta2O5, and the zirconium oxide composition uses a raw material whose main crystal phase of ZrO2 is monoclinic and has machinability.

[0015] Prior art literature

[0016] Patent Literature

[0017] Patent Document 1: Japanese Patent Application Publication No. 2015-127294

[0018] Patent Document 2: International Publication No. 2021 / 132644 Summary of the invention

[0019] Problems to be solved by the invention

[0020] The zirconia sintered bodies disclosed in Patent Documents 1 and 2 can be machined even in a sintered state. However, the processing time for cutting out a dental prosthesis is long, and there is still room for improvement from the viewpoint of shortening the treatment time.

[0021] In addition, although the zirconia sintered bodies disclosed in Patent Documents 1 and 2 can be machined, the number of dental prostheses obtained by continuous processing using one processing tool is small, and the processing tool is consumed quickly. Therefore, there are the following problems: the frequency of replacing the processing tool increases, the tool replacement time increases, and the productivity and economic efficiency decrease.

[0022] Furthermore, if the hardness of the material is reduced in order to improve machinability, there is a problem that the strength of the material is reduced.

[0023] An object of the present invention is to provide a dental workpiece having strength suitable for dental use and excellent machinability in a sintered state.

[0024] In addition, an object of the present invention is to provide a dental workpiece that can be machined in a sintered state, has a short machining time, can suppress consumption of machining tools, can produce a large number of dental prostheses by continuous machining using one machining tool, and has excellent productivity and economy.

[0025] Means used to solve problems

[0026] The inventors of the present invention have repeatedly conducted in-depth studies to solve the above-mentioned problems, and as a result, found that for a dental workpiece having a biaxial bending strength of 300 MPa or more, in a particle spraying test, when a spherical alumina slurry having an average particle size of 3.0 μm is projected, the erosion rate is 8.0 μm / g or more, or the value of the erosion rate (μm / g) × the average grain size (μm) is 15 μm. 2 / g or more, the problem can be solved, and further studies have been conducted based on this finding to complete the present invention.

[0027] That is, the present invention includes the following technical solutions.

[0028] [1] A workpiece for dental use, wherein, in a particle spraying test, when a spherical alumina slurry having an average particle size of 3.0 μm is projected, the erosion rate is 6.5 μm / g or more, or the value of the erosion rate (μm / g) × the average grain size (μm) is 15 μm 2 / g or above,

[0029] The biaxial bending strength measured according to ISO6872:2015 is 300 MPa or more.

[0030] [2] The dental workpiece according to [1], wherein in a fine particle spraying test, when a spherical alumina slurry having an average particle size of 3.0 μm is projected, the erosion rate is 8.0 μm / g or more.

[0031] [3] The dental workpiece according to [1] or [2], wherein the dental workpiece is a ceramic sintered body.

[0032] [4] The dental workpiece according to [3], wherein the ceramic sintered body is a sintered body containing zirconium oxide.

[0033] [5] The dental workpiece according to any one of [1] to [4], wherein the average grain size of the dental workpiece is 0.05 to 15.0 μm.

[0034] [6] A dental workpiece according to any one of [1] to [5], wherein in a particle spraying test, when a spherical alumina slurry having an average particle size of 3.0 μm is projected, the value of the erosion rate (μm / g) × the average grain size (μm) is 15 μm 2 / g or above.

[0035] [7] The dental workpiece according to [5], wherein in a particle spraying test, when a spherical alumina slurry having an average particle size of 3.0 μm is projected, the value of the erosion rate (μm / g) × average grain size (μm) is 15 μm 2 / g or more, and the average grain size of the dental workpiece is 3.0 μm to 15.0 μm.

[0036] [8] The dental workpiece according to [5], wherein in a particle spraying test, the erosion rate when projecting spherical alumina slurry with an average particle size of 3.0 μm is 8.0 μm / g or more, and the average grain size of the dental workpiece is 0.05 μm to 5.0 μm.

[0037] Effects of the Invention

[0038] According to the present invention, a dental workpiece can be provided which has strength suitable for dental use and is excellent in machinability in a sintered state.

[0039] Furthermore, according to the present invention, a dental workpiece having light transmittance for dental use can be provided.

[0040] Furthermore, according to the present invention, in the case where the dental workpiece is a sintered body containing zirconium oxide or a sintered body containing aluminum oxide, it is possible to provide a dental workpiece that can be machined in a sintered body state, has a short machining time, can suppress the consumption of machining tools, can produce a large number of dental restorations through continuous processing using one machining tool (hereinafter also referred to as "continuous processing"), and has excellent productivity and economy. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is a schematic diagram showing the impact state of spherical alumina in the MSE test of the present invention.

[0042] Figure 2 This is a schematic diagram showing an example of an MSE test apparatus used in the MSE test of the present invention. DETAILED DESCRIPTION

[0043] The dental workpiece of the present invention has an erosion rate of 6.5 μm / g or more when a spherical alumina slurry having an average particle size of 3.0 μm is projected in a micro slurry spraying (MSE) test (hereinafter referred to as the "MSE test"), or a value of erosion rate (μm / g) × average grain size (μm) of 15 μm. 2 / g or above,

[0044] The biaxial bending strength measured according to ISO6872:2015 is 300 MPa or more.

[0045] The dental workpiece of the present invention is preferably a ceramic sintered body. Examples of the ceramic sintered body include a sintered body containing zirconium oxide and a sintered body containing aluminum oxide.

[0046] Hereinafter, a sintered body containing zirconium oxide and having excellent machinability in a sintered body state is also referred to as a "machinable zirconium oxide composite sintered body".

[0047] As a preferred embodiment, the following dental workpiece can be cited, wherein the ceramic sintered body is a sintered body containing zirconium oxide. The sintered body containing zirconium oxide means that ZrO2 particles (powder) are in a completely sintered state (sintered state).

[0048] In addition, in this specification, the upper limit value and the lower limit value of the numerical range (content of each component, ratio calculated from each component, value, each physical property, etc.) can be combined appropriately.

[0049] In this specification, machining includes cutting and grinding. In addition, the machining may be either wet machining or dry machining, and is not particularly limited.

[0050] Regarding the dental workpiece of the present invention, from the viewpoint of being able to have both excellent strength for dental use and machinability in the sintered body state, in the MSE test, (i) the erosion rate when projecting spherical alumina slurry with an average particle size of 3.0 μm is 6.5 μm / g or more or (ii) the value of erosion rate (μm / g)×average grain size (μm) is 15 μm. 2 / gAt least any one of the above.

[0051] The dental workpiece of the present invention can satisfy both (i) and (ii).

[0052] In a certain suitable embodiment (hereinafter also referred to as embodiment (A)), with respect to the dental workpiece of the present invention, from the viewpoint of being able to have both excellent strength for dental use and machinability in a sintered body state, in an MSE test, the erosion rate when projecting spherical alumina slurry with an average particle size of 3.0 μm is 6.5 μm / g or more, preferably 8.0 μm / g or more, more preferably 8.5 μm / g or more, and from the viewpoint of better machinability in a sintered body state, it is further preferably 9.0 μm / g or more, particularly preferably 10.0 μm / g or more, and most preferably 12.0 μm / g or more.

[0053] In embodiment (A), the upper limit of the erosion rate is not particularly limited as long as the effects of the present invention are exhibited, but is preferably 100.0 μm / g or less, more preferably 60.0 μm / g or less, further preferably 40.0 μm / g or less, and particularly preferably 30.0 μm / g or less.

[0054] In embodiment (A), it can be inferred that: by making the erosion rate of the dental workpiece of the present invention within the aforementioned range, when the dental workpiece is, for example, a ceramic sintered body (suitably a sintered body containing zirconia), the strength of the interface of the particles constituting the sintered body (hereinafter also referred to as "grain boundary") can be weakened within a range suitable for dental use, the machinability in the sintered body state is excellent, the machining time based on mechanical machining can be shortened, the consumption of machining tools can be suppressed, and the number of dental restorations that can be cut out by continuous machining can be increased.

[0055] Furthermore, by setting the erosion rate within the above range, the grain boundary strength can be weakened, and the machinability in the sintered body state is excellent. On the other hand, the strength suitable for dental use is not impaired, and both strength and machinability in the sintered body state can be achieved.

[0056] The MSE test method (hereinafter also referred to as the "slurry-based fabric jet abrasion method") is one of the test methods for evaluating the mechanical properties of materials at an energy scale using a microparticle projection processing technique.

[0057] In the MSE test method, the impact velocity corresponds to the energy of the particle impact under specified conditions, and the wear amount at this time represents the strength of the material.

[0058] In the MSE test method, a device is used that combines the wear damage part based on particle impact and the shape measurement part of the projection mark (erosion mark). A schematic diagram showing the impact of spherical aluminum oxide in the MSE test method is shown in Figure 1 .exist Figure 1In the process, the spherical alumina 1 projected from the projection nozzle hits the sintered body 2, and the sintered body 2 is cut. The projection mark (erosion mark) obtained by the projection of the spherical alumina 1 is measured by the shape measuring unit. Figure 1 is from Figure 2 This is a partially enlarged view of a spherical aluminum oxide 1 projected by a projection gun 42 having a projection nozzle 50 onto a sintered body 2 as a sample W.

[0059] Examples of the MSE test apparatus include an apparatus including a projection unit having a projection gun and a projection nozzle, a shape measuring unit (a unit for acquiring the contour of a projection trace), and a data processing unit. Figure 2 .

[0060] exist Figure 2 In the slurry local injection abrasion device 10 , the slurry 34 is stored in a slurry tank 35 and stirred by a stirrer 36 .

[0061] The slurry pressure is applied from the compressed air source 38 to the slurry tank 35 via the slurry pressure regulating valve 40 , so that the slurry 34 from the slurry tank 35 is supplied to the projection gun 42 via the slurry flow meter 44 .

[0062] In addition, gas pressure is supplied from the compressed air source 38 to the projection gun 42 via a gas pressure regulating valve 46 and a gas flow meter 48 .

[0063] The projection nozzle 50 disposed at the lower part of the projection gun 42 has a projection cross-sectional area of ​​1.0 mm 2 The nozzle (1 mm in length×1 mm in width) is covered by the projection container 54 .

[0064] The projection gun 42 mixes the supplied slurry 34 with gas and sprays it from the projection nozzle 50 at a projection distance of 4 mm toward the dental workpiece sample W fixed by the fixture 52 , thereby partially abrading the surface of the dental workpiece sample W to form a depression.

[0065] The jig 52 to which the sample W of the dental workpiece is fixed is moved in and out of the projection container 54 by the base driving device 56. The slurry 34 stored in the projection container 54 is returned to the slurry tank 35 by the recovery pump 58.

[0066] As the MSE test apparatus, a known apparatus (for example, a slurry local jet abrasion apparatus (MSR-A model, manufactured by Palmeso Corporation)) can be used.

[0067] In the MSE test of this specification, a slurry in which spherical alumina having an average particle size of 3.0 μm is dispersed is projected onto a dental workpiece, which is a sintered body, to destroy the grain boundaries. The erosion rate is calculated using the following formula using the depth of the sintered body cut by the destruction.

[0068] Erosion rate 〔μm / g〕=cutting depth 〔μm〕÷projected slurry mass 〔g〕

[0069] The measurement conditions of the MSE test in this specification are as described in the examples described below. As spherical alumina, a commercially available product (for example, model: MSE-BA-3-3, manufactured by Palmeso) can be used.

[0070] The average particle size of the spherical alumina slurry used in the MSE test can be measured on a volume basis using, for example, a laser diffraction particle size distribution analyzer (SALD-2300: manufactured by Shimadzu Corporation) using a 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium.

[0071] Hereinafter, the embodiment will be described by taking the case where the dental workpiece in embodiment (A) is a sintered body containing zirconium oxide as an example. The dental workpiece of the present invention is not limited to a sintered body containing zirconium oxide, and therefore, unless otherwise stated, the sintered body containing zirconium oxide can be understood as a sintered body containing aluminum oxide.

[0072] The sintered body containing zirconium oxide preferably contains ZrO 2 , HfO 2 and a stabilizer capable of suppressing phase transformation of zirconium oxide, and contains Nb 2 O 5 and / or Ta 2 O 5 , and further contains a Group I element as required.

[0073] Hereinafter, as a suitable embodiment, the embodiment is described by taking the following sintered body containing zirconium oxide as an example, wherein the sintered body contains ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconium oxide (hereinafter also referred to as "stabilizer"), Nb2O5 and / or Ta2O5, and further contains Group I elements as needed.

[0074] In a sintered body containing zirconium oxide, the total content of ZrO2 and HfO2 in a total of 100 mol% of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5 is preferably 78 to 97.5 mol%. From the viewpoint of better light transmittance and strength, it is more preferably 79 mol% or more and 96 mol% or less, further preferably 80 mol% or more and 94 mol% or less, and particularly preferably 81 mol% or more and 93 mol% or less.

[0075] In a sintered body containing aluminum oxide, the content of Al2O3 in the total 100 mol% of Al2O3, Nb2O5 and Ta2O5 can be understood as the total content of ZrO2 and HfO2 in the aforementioned sintered body containing zirconium oxide. As a suitable embodiment, the content of Al2O3 in the aforementioned total 100 mol% is preferably 78 to 99 mol%. From the viewpoint of better light transmittance and strength, it is more preferably 80 mol% or more and 98.8 mol% or less, further preferably 82 mol% or more and 98.5 mol% or less, and particularly preferably 83 mol% or more and 98.4 mol% or less.

[0076] It should be noted that the sintered body containing alumina does not need to contain a stabilizer.

[0077] Examples of stabilizers that can inhibit the phase transition of zirconium oxide include calcium oxide (CaO), magnesium oxide (MgO), yttrium oxide (Y2O3), cerium oxide (CeO2), scandium oxide (Sc2O3), lanthanum oxide (La2O3), erbium oxide (Er2O3), praseodymium oxide (Pr2O3, Pr6O3), and vanadium oxide (Er2O3). 11 ), samarium oxide (Sm2O3), europium oxide (Eu2O3), thulium oxide (Tm2O3), gallium oxide (Ga2O3), indium oxide (In2O3) and ytterbium oxide (Yb2O3) and the like, preferably Y2O3 (yttrium trioxide) and / or CeO2 from the viewpoint of better effect of the present invention, especially excellent aesthetics. The aforementioned stabilizer may be used alone or in combination of two or more.

[0078] In a sintered body containing zirconium oxide, the content of the stabilizer capable of inhibiting the phase transformation of zirconium oxide is preferably 1 to 12 mol%, more preferably greater than 2 mol% and less than 10 mol%, and from the viewpoint of better light transmittance and strength, further preferably greater than 3 mol% and less than 8 mol%, and particularly preferably greater than 3.5 mol% and less than 7.5 mol%.

[0079] As a preferred embodiment, there is a sintered body containing zirconium oxide, wherein the stabilizer capable of suppressing the phase transformation of zirconium oxide contains Y2O3 and / or CeO2, and the total content of Y2O3 and CeO2 is 2 mol% or more and 10 mol% or less.

[0080] As another suitable embodiment, there can be mentioned a sintered body containing zirconium oxide, wherein the stabilizer capable of suppressing the phase transformation of zirconium oxide contains Y 2 O 3 , and the content of Y 2 O 3 is 2 mol % or more and 10 mol % or less.

[0081] In any of the aforementioned embodiments, the contents of Y2O3 and CeO2 can be appropriately changed within the range described in this specification. For example, from the viewpoint of better light transmittance and strength, the total content of Y2O3 and CeO2 can be greater than 2.5 mol% and less than 10 mol%, or greater than 3 mol% and less than 9 mol%.

[0082] The reason why a sintered body containing zirconium oxide can obtain an erosion rate within the above range, has strength and light transmittance suitable for dental applications, and has high machinability and can be machined in the sintered state is not yet clear, but can be presumed as follows.

[0083] It can be speculated that in a sintered body containing zirconium oxide, which contains ZrO2, HfO2 and a stabilizer capable of inhibiting the phase transformation of zirconium oxide, contains Nb2O5 and / or Ta2O5, and further contains a Group I element, the Group I element further exists in the grain boundaries of the zirconium oxide particles, so that the Group I element reduces the grain boundary strength, acts in a direction that facilitates the separation of the particles from each other, and is easy to cut. By keeping the erosion rate within the aforementioned range, the reduction in strength is suppressed, and the machinability in the sintered body state (especially the machinability in continuous processing) is improved.

[0084] In addition, it is inferred that in a sintered body containing Nb2O5 and / or Ta2O5 and containing zirconium oxide, Nb2O5 and / or Ta2O5 coarsen the microstructure and act in the direction of reducing the hardness, so the Group I element is integrated with Nb2O5 and / or Ta2O5 and acts in the direction of improving the machinability. Therefore, the Group I element is integrated with Nb2O5 and / or Ta2O5 and acts to have the strength required for artificial teeth and can impart excellent free-machining properties, so that the erosion rate within the above range can be obtained. The erosion rate within the above range can shorten the machining time by machining in the sintered body state, and on this basis, it can suppress the consumption of machining tools, and can increase the number of dental prostheses obtained by continuous machining using one machining tool, and can also solve the problems peculiar to the sintered body in continuous machining.

[0085] On the other hand, it can be speculated that in a sintered body containing zirconium oxide that does not contain Nb2O5 and / or Ta2O5, by increasing the content of the Group I element and other adjustments, the Group I element is further present in the grain boundaries of the zirconium oxide particles. As a result, the Group I element reduces the grain boundary strength and acts in a direction that facilitates the separation of the particles from each other, making it easy to cut. By keeping the erosion rate within the aforementioned range, the reduction in strength is suppressed, and the machinability in the sintered body state (especially the machinability in continuous processing) is improved.

[0086] In the sintered body containing zirconium oxide of the present invention, the Group I element functions as a free-machining agent as described above, and an erosion rate within the above-mentioned range can be obtained without significantly impairing strength and light transmittance.

[0087] The content of the Group I element contained in the sintered body containing zirconium oxide of the present invention (especially a sintered body containing Nb2O5 and / or Ta2O5) is preferably more than 0 mol% and not more than 3 mol%. From the viewpoint of further excellent machinability in the sintered body state and the ability to further increase the number of dental prostheses that can be continuously processed using one processing tool, it is more preferably from 0.05 mol% to 3 mol%. From the viewpoint of particularly excellent machinability in the sintered body state and the ability to further shorten the processing time by machining, it is further preferably from 0.06 mol% to 2.5 mol%, particularly preferably from 0.07 mol% to 1.0 mol%, and most preferably from 0.08 mol% to 0.34 mol%.

[0088] In the sintered body containing aluminum oxide, the content of the Group I element can also be within the above range.

[0089] As another suitable embodiment, the content of the Group I element contained in the sintered body containing zirconium oxide without containing Nb2O5 and / or Ta2O5 is preferably from 0.5 mol% to 6 mol%, from the viewpoint of better machinability in the sintered body state and further increasing the number of dental prostheses that can be continuously processed using one processing tool, it is more preferably from 0.8 mol% to 5 mol%, further preferably from 1.0 mol% to 4.0 mol%, particularly preferably from 1.2 mol% to 3.5 mol%, and most preferably from 1.5 mol% to 3.0 mol%.

[0090] Examples of the Group I element include Li, Na, K, Rb, Cs, and Fr, and Li, Na, and K are preferred from the viewpoint of further improving the machinability in the sintered body state. The Group I element may be used alone or in combination of two or more.

[0091] As described above, since the Group I element functions as a whole with Nb2O5 and / or Ta2O5, the effect of the aforementioned stabilizer is not impaired. Therefore, the aforementioned stabilizer is not particularly limited and the effect of the present invention is exerted.

[0092] In the sintered body containing zirconium oxide of the present invention, the total content of Nb2O5 and Ta2O5 in the total of 100 mol% of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5 is preferably 1 to 9 mol%, more preferably 1.5 mol% or more and 8.5 mol% or less. From the viewpoint of acting as a whole with the Group I elements and having better machinability in the sintered body state, it is further preferably 2.5 mol% or more and 8 mol% or less, and particularly preferably 3 mol% or more and 7 mol% or less.

[0093] When the total content of Nb2O5 and Ta2O5 is 1 mol% or more, sufficient machinability in the sintered body state is easily obtained. In addition, when the total content of Nb2O5 and Ta2O5 is 9 mol% or less, the occurrence of defects in the obtained dental workpiece is suppressed, and sufficient physical properties are easily obtained.

[0094] In the sintered body containing alumina of the present invention, the total content of Nb2O5 and Ta2O5 in the total 100 mol% of Al2O3, Nb2O5 and Ta2O5 is preferably 0.5 mol% to 9 mol%, more preferably 0.8 mol% to 8.5 mol%. From the viewpoint of acting as a whole with the Group I elements and having better machinability in the sintered body state, it is further preferably 1.0 mol% to 8 mol%, and particularly preferably 1.5 mol% to 7 mol%.

[0095] When the total content of Nb2O5 and Ta2O5 is 0.5 mol% or more, sufficient machinability in the sintered body state is easily obtained. In addition, when the total content of Nb2O5 and Ta2O5 is 9 mol% or less, the occurrence of defects in the obtained dental workpiece is suppressed, and sufficient physical properties are easily obtained.

[0096] As described above, Nb2O5 and Ta2O5 coarsen the fine structure and work in the direction of reducing the hardness. They work together with the Group I elements to impart excellent free-machining properties. On this basis, the sintering density is maximized through interaction with other components (such as TiO2 and Al2O3) added to the sintered body containing zirconia and the application of HIP, thereby ensuring the aesthetics of natural teeth.

[0097] In this specification, the content rate of each component in the dental workpiece can be calculated from the charge amount of the raw material.

[0098] In addition, the content of each component of ZrO2, HfO2, stabilizer, Nb2O5 and Ta2O5 in the dental workpiece can also be measured by, for example, inductively coupled plasma (ICP) emission spectrometry, fluorescent X-ray analysis, etc.

[0099] The content rate (mol%) of the Group I element is the external addition rate relative to the total of 100 mol% of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5. Therefore, the content rate of the Group I element in the dental workpiece can be calculated by converting the feed amount (mass) of the raw material at the time of addition into mol%.

[0100] In addition, the content rate (mass %) of the zirconium oxide strengthening agent is the external addition rate relative to the total of 100 mass % of ZrO2, HfO2, the above-mentioned stabilizer, Nb2O5 and Ta2O5. Therefore, the content rate of the zirconium oxide strengthening agent in the dental workpiece can be calculated based on the feed amount (mass) of the raw materials when adding.

[0101] The content of each component of ZrO2, HfO2, stabilizer, Nb2O5 and Ta2O5 is a ratio in the total of 100 mol% of ZrO2, HfO2, stabilizer, Nb2O5 and Ta2O5, and the total of ZrO2, HfO2, stabilizer, Nb2O5 and Ta2O5 does not exceed 100 mol%. For example, when the raw material composition contains Nb2O5 but does not contain Ta2O5, the content of each component of ZrO2, HfO2, stabilizer and Nb2O5 refers to the content ratio relative to the total of 100 mol% of ZrO2, HfO2, stabilizer and Nb2O5.

[0102] In addition, when the content of the stabilizer is set to A mol% and the total content of Nb2O5 and Ta2O5 is set to B mol%, from the viewpoint of machinability, the ratio of A / B is preferably greater than or equal to 0.9 and less than or equal to 3, and more preferably greater than or equal to 0.95 and less than or equal to 2. From the viewpoint of improving the effect of the Group I element and Nb2O5 and / or Ta2O5 functioning as a whole, being able to impart better free machinability, being able to suppress the consumption of processing tools, and being able to further increase the number of dental prostheses obtained by continuous processing using one processing tool, it is further preferably greater than or equal to 1 and less than or equal to 1.6.

[0103] As a preferred embodiment (A-1), there can be mentioned a dental workpiece, wherein in a fine particle spraying test, an erosion rate when a spherical alumina slurry having an average particle size of 3.0 μm is projected is 8.0 μm / g or more,

[0104] The biaxial bending strength measured according to ISO6872:2015 is more than 300MPa.

[0105] The dental workpiece contains ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconium oxide, and contains Nb2O5 and / or Ta2O5.

[0106] In the total of 100 mol% of ZrO2, HfO2, the above-mentioned stabilizer, Nb2O5 and Ta2O5, the total content of ZrO2 and HfO2 is 78 to 97.5 mol%,

[0107] The content of the stabilizer is 1 to 12 mol%.

[0108] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.

[0109] It also contains Group I elements,

[0110] The aforementioned stabilizer comprises Y2O3 and / or CeO2,

[0111] The content of the Group I element is greater than 0 mol% and less than 3 mol% relative to 100 mol% of the total of ZrO2, HfO2, the stabilizer, Nb2O5 and Ta2O5,

[0112] When the content of the above-mentioned stabilizer is set to A mol % and the total content of Nb 2 O 5 and Ta 2 O 5 is set to B mol %, A / B is greater than or equal to 0.9 and less than or equal to 3.

[0113] As an embodiment (A-2) of the present invention, the following dental workpiece can be listed, which contains ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconia and a Group I element, and contains Nb2O5 and / or Ta2O5, and on this basis, also contains a zirconia strengthener.

[0114] The zirconia strengthener refers to a strength improver that works together with the Group I element in a dental workpiece containing ZrO2, HfO2 and a stabilizer that can inhibit the phase transformation of zirconia and contains Nb2O5 and / or Ta2O5 to improve the strength of the sintered body.

[0115] In the dental workpiece containing zirconium oxide strengthening agent, as described above, the total content of ZrO2 and HfO2, the type and content of stabilizer, the total content of Nb2O5 and Ta2O5, the type and content of Group I elements, and the A / B ratio can be appropriately changed.

[0116] In a dental workpiece containing a zirconia reinforcing agent, the content of the zirconia reinforcing agent is preferably greater than 0 mass % and less than 5.0 mass % relative to the total of 100 mass % of ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconia, and Nb2O5 and Ta2O5. From the viewpoint of functioning as a whole when combined with the Group I elements and having better strength, it is more preferably greater than 0.01 mass % and less than 4.5 mass %, and further preferably greater than 0.5 mass % and less than 4.0 mass %.

[0117] Examples of the zirconium oxide reinforcing agent include TiO 2 and Al 2 O 3 . The zirconium oxide reinforcing agent may be used alone or in combination of two or more.

[0118] As another preferred embodiment, in any of the above embodiments, there can be mentioned a dental workpiece, wherein the zirconium oxide reinforcing agent contains TiO 2 and the content of TiO 2 is 0.6 to 3.7% by mass.

[0119] As a preferred embodiment, there can be mentioned a dental workpiece, wherein in a fine particle spraying test, an erosion rate when a spherical alumina slurry having an average particle size of 3.0 μm is projected is 8.0 μm / g or more,

[0120] The biaxial bending strength measured according to ISO6872:2015 is more than 300MPa.

[0121] The dental workpiece contains ZrO2, HfO2 and a stabilizer capable of inhibiting the phase transformation of zirconium oxide, and contains Nb2O5 and / or Ta2O5.

[0122] In the total of 100 mol% of ZrO2, HfO2, the above-mentioned stabilizer, Nb2O5 and Ta2O5, the total content of ZrO2 and HfO2 is 78 to 97.5 mol%,

[0123] The content of the stabilizer is 1 to 12 mol%.

[0124] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.

[0125] It also contains Group I elements,

[0126] The aforementioned stabilizer comprises Y2O3 and / or CeO2,

[0127] The zirconium oxide reinforcing agent contains TiO2, and the content of TiO2 is 0.6 to 3.7% by mass.

[0128] The content of the Group I element is greater than 0 mol% and less than 3 mol% relative to 100 mol% of the total of ZrO2, HfO2, the stabilizer, Nb2O5 and Ta2O5,

[0129] When the content of the above-mentioned stabilizer is set to A mol % and the total content of Nb 2 O 5 and Ta 2 O 5 is set to B mol %, A / B is greater than or equal to 0.9 and less than or equal to 3.

[0130] As described above, by setting the erosion rate within the above range, the steel sheet has strength suitable for dental applications in various compositions and is excellent in machinability in a sintered body state (particularly machinability in continuous processing).

[0131] The average grain size of the dental workpiece of the present invention is preferably 0.05 to 15.0 μm, more preferably 0.1 to 10.0 μm, further preferably 0.3 to 7.0 μm, and particularly preferably 0.5 to 5.0 μm from the viewpoint of better machinability, strength, and light transmittance in the sintered state. The method for measuring the average grain size is described in the examples described below.

[0132] The average grain size can be measured by adjusting the number of particles so that the number of particles included in the SEM photograph image of one field of view is about 50 or 100.

[0133] In embodiment (A), from the viewpoint that the energy brought by the transmitted alumina particles is effectively used for grain boundary destruction and the machinability in the sintered state is excellent, the average grain size of the dental workpiece is preferably 0.05 μm to 5.0 μm, and from the viewpoint of better machinability, strength and light transmittance in the sintered state, it is more preferably 0.08 to 4.0 μm, further preferably 0.1 to 3.5 μm, and particularly preferably 0.3 to 3.0 μm.

[0134] In a certain preferred embodiment (hereinafter also referred to as embodiment (B)), from the viewpoint of being able to have both excellent strength for dental use and machinability in the sintered body state, the dental workpiece of the present invention, in the MSE test, when a spherical alumina slurry with an average particle size of 3.0 μm is projected, the value of the erosion rate (μm / g)×average grain size (μm) is 15 μm. 2 / g or more, preferably 20 μm from the viewpoint of better machinability in the sintered state 2 / g or more, more preferably 23 μm 2 / g or more, more preferably 25 μm 2 / g or more, particularly preferably 30 μm 2 / g or above.

[0135] In the embodiment (B), the upper limit of the erosion rate (μm / g)×average grain size (μm) is not particularly limited as long as the effect of the present invention is exhibited, but is preferably 100 μm. 2 / g or less, more preferably 80 μm 2 / g or less, more preferably 65 μm 2 / g or less, particularly preferably 50 μm 2 / g or less.

[0136] The MSE test method, MSE test apparatus, and the measurement method and measurement conditions of the erosion rate (μm / g) and the average grain size (μm) in the embodiment (B) are the same as those in the embodiment (A).

[0137] In embodiment (B), the average grain size of the dental workpiece can be 0.05 to 15.0 μm. From the viewpoint of excellent machinability in the sintered body state, it is preferably 3.0 to 15.0 μm, more preferably 4.0 to 15.0 μm, further preferably 5.0 to 15.0 μm, and particularly preferably 5.5 to 15.0 μm.

[0138] In implementation (B), it can be inferred that: although the dental workpiece of the present invention does not contain Group I elements, the erosion rate (μm / g) × average grain size (μm) is adjusted to be within the aforementioned range by significantly extending the firing time when making a single sintered body. Therefore, when the dental workpiece is, for example, a ceramic sintered body (suitably a sintered body containing zirconia), the strength of the interface of the particles constituting the sintered body (hereinafter also referred to as "grain boundary") can be weakened within a range suitable for dental use, the machinability in the sintered body state is excellent, the machining time based on mechanical machining can be shortened, the consumption of machining tools can be suppressed, and the number of dental restorations that can be cut out by continuous machining can be increased.

[0139] Regarding the erosion rate (μm / g)×average grain size (μm), the denominator (g) in the unit of the erosion rate (μm / g) refers to the mass of the alumina slurry sprayed per unit time. Since the alumina slurry is sprayed on the sample at a constant speed on average, it can be considered as work for the sample. The numerator (μm) is the measured value of the depth of the sample cut by spraying the alumina slurry.

[0140] That is, the average grain size × erosion rate can be said to be the ratio of the unit area (μm) that can be removed per unit time. 2 ) energy (μm 2 / W) have the same meaning.

[0141] Therefore, it can be said that this value is correlated with the machinability, and further, in the dental workpiece of the present invention, when the erosion rate (μm / g)×average grain size (μm) is within the above range, the machinability is significantly improved.

[0142] In addition, in the dental workpiece of the present invention, the grain boundary strength is weakened by making the erosion rate (μm / g) × average grain size (μm) within the aforementioned range, and the machinability in the sintered state is excellent. On the other hand, the strength suitable for dental use is not impaired, and both strength and machinability in the sintered state can be achieved.

[0143] In the embodiment (B), the erosion rate may be 8.0 μm / g or more, less than 8.0 μm / g, or 6.5 μm / g or more, less than 6.5 μm / g, or less than 6.0 μm / g, without particular limitation.

[0144] In the embodiment (B), as long as the effects of the present invention can be obtained, the erosion rate may be overlapped with that of the embodiment (A), or the erosion rate of the embodiment (A) may be eliminated.

[0145] In the embodiment (B), when the erosion rate is 6.5 μm / g or more, the appropriate erosion rate of the embodiment (A) can be appropriately set.

[0146] Hereinafter, the embodiment will be described by taking as an example a case where the dental workpiece in the embodiment (B) is a sintered body containing zirconium oxide.

[0147] The dental workpiece of the present invention is not limited to a sintered body containing zirconium oxide, and therefore, the sintered body containing zirconium oxide can be understood as a sintered body containing aluminum oxide, for example.

[0148] As a suitable embodiment (B-1), the following sintered body containing zirconium oxide can be listed, wherein the sintered body containing zirconium oxide in embodiment (B) contains ZrO2, HfO2 and a stabilizer capable of inhibiting the phase transformation of zirconium oxide, contains Nb2O5 and / or Ta2O5, and further contains Group I elements as needed.

[0149] In addition, as another suitable embodiment (B-2), the following sintered body containing zirconium oxide can be listed, which does not contain Group I elements, contains ZrO2, HfO2 and a stabilizer capable of inhibiting the phase transformation of zirconium oxide, and contains Nb2O5 and / or Ta2O5.

[0150] Regarding the total content of ZrO2 and HfO2 in embodiment (B) including embodiments (B-1) and (B-2), the type and content of the stabilizer capable of inhibiting the phase transformation of zirconia, the total content of Nb2O5 and Ta2O5, the type and content of Group I elements, the ratio of A / B when the content of the stabilizer is set to Amol% and the total content of Nb2O5 and Ta2O5 is set to Bmol%, and the type and content of the zirconia strengthening agent, it is the same as in embodiment (A).

[0151] In any of the embodiments (A) and (B), the density of the processable zirconia composite sintered body is preferably 5.5 g / cm2 from the viewpoint that the higher the density, the fewer internal voids there are, the less likely light is to be scattered, the higher the light transmittance is, and the higher the strength is. 3 More preferably, 5.7 g / cm 3 More preferably, 5.9 g / cm 3 above.

[0152] It is particularly preferred that the workable zirconia composite sintered body contains substantially no voids.

[0153] The density of the composite sintered body can be calculated using (mass of the composite sintered body) / (volume of the composite sintered body).

[0154] In an embodiment of the sintered body including zirconium oxide, as a method for producing a dental workpiece of the present invention, for example, the following method for producing a dental workpiece can be cited, which comprises:

[0155] A step of preparing a molded body using a raw material composition, wherein the raw material composition comprises ZrO2, HfO2 and a stabilizer capable of inhibiting phase transformation of zirconium oxide, and comprises Nb2O5 and / or Ta2O5, wherein the total content of ZrO2 and HfO2 is 78 to 97.5 mol%, the content of the stabilizer is 1 to 12 mol%, the total content of Nb2O5 and Ta2O5 is 1 to 9 mol%, and further comprises a raw material compound of a Group I element as required; and

[0156] A step of sintering the molded body.

[0157] In the following, except for the cases described separately, each condition can be applied to any embodiment of the manufacturing method. For example, in the embodiment of the sintered body containing aluminum oxide, in the manufacturing method of the dental workpiece in which the dental workpiece is a sintered body containing zirconium oxide, ZrO2 and HfO2 are replaced with Al2O3, the aforementioned stabilizer is not included, and the content of each component is adjusted within the range described in this specification. Changes such as changes can be made, thereby enabling the same manufacturing.

[0158] The raw material composition for manufacturing the dental workpiece includes ZrO2, HfO2 and a stabilizer capable of inhibiting the phase transition of zirconium oxide, and includes Nb2O5 and / or Ta2O5, and further includes a raw material compound of the first group element as required. The raw material composition for manufacturing the dental workpiece can be in a dry state, or in a state containing a liquid or in a state contained in a liquid. The raw material composition can be in the form of, for example, powder, granules or granules, paste, slurry, etc.

[0159] In a preferred embodiment, in order to make the obtained dental workpiece contain a Group I element, the raw material composition contains a raw material compound of the Group I element. Examples of the raw material compound of the Group I element include hydroxides and / or salts of the Group I element.

[0160] In another suitable embodiment, the feedstock composition does not contain feedstock compounds of Group I elements.

[0161] When the raw material composition does not contain a raw material compound of a Group I element, the value of the erosion rate (μm / g)×average grain size (μm) can be adjusted to within a specified range by significantly extending the sintering temperature (maximum sintering temperature) for sintering the molded body described later.

[0162] Examples of the hydroxide of the Group I element include lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, and francium hydroxide.

[0163] Examples of salts of Group I elements include carbonates and hydrogen carbonates.

[0164] Examples of the carbonate of the Group I element include lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, francium carbonate, and cesium carbonate.

[0165] Examples of the hydrogen carbonate salt of the Group I element include lithium hydrogen carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, rubidium hydrogen carbonate, francium hydrogen carbonate, and cesium hydrogen carbonate.

[0166] The hydroxide and salt of the Group I element may be used alone or in combination of two or more.

[0167] Regarding ZrO2 and HfO2, commercially available zirconium oxide powder can be used. Examples of commercially available products include zirconium oxide powder (trade name "Zpex (registered trademark)" (content of Y2O3: 3 mol%), "Zpex (registered trademark) 4" (content of Y2O3: 4 mol%), "Zpex (registered trademark) 4Smile (registered trademark)" (content of Y2O3: 5.5 mol%), "TZ-3Y" (content of Y2O3: 3 mol%), "TZ-3YS" (content of Y2O3: 3 mol%), "TZ-4YS" (content of Y2O3: 4 mol%), "TZ-6Y" (content of Y2O3: 6 mol%), "TZ-6YS" (content of Y2O3: 6 mol%), "TZ-8YS" (content of Y2O3: 8 mol%), " TZ-10YS" (content of Y2O3: 10 mol%), "TZ-3Y-E" (content of Y2O3: 3 mol%), "TZ-3YS-E" (content of Y2O3: 3 mol%), "TZ-3YB-E" (content of Y2O3: 3 mol%), "TZ-3YSB-E" (content of Y2O3: 3 mol%), "TZ-3YB" (content of Y2O3: 3 mol%), "TZ-3YSB" (content of Y2O3: 3 mol%), "TZ-3Y20AB" (content of Y2O3: 3 mol%), "TZ-8YSB" (content of Y2O3: 8 mol%), "TZ-0" (content of Y2O3: 0 mol%); all of the above are manufactured by Tosoh Corporation), etc. The aforementioned commercially available zirconium oxide powder also includes HfO2. As a commercial product, a product further containing Y2O3 may also be used. As the zirconium oxide powder, the raw material composition of the present invention may also use a zirconium oxide powder in which Y2O3 is uniformly dispersed and solid-dissolved, such as the aforementioned commercial product TZ series (part of the trade name includes "TZ").

[0168] The method for producing the zirconium oxide powder is not particularly limited, and a known method such as a breakdown process of pulverizing coarse particles into fine powder and a building up process of synthesizing atoms or ions using a nucleus formation and growth process can be used.

[0169] The type of zirconium oxide powder in the raw material composition is not particularly limited. When the zirconium oxide powder contains ZrO2 and HfO2 but does not contain a stabilizer, or when the content of the stabilizer is increased as needed, stabilizer particles can be added separately. The stabilizer particles are not particularly limited as long as the content of the stabilizer contained in the dental workpiece can be adjusted to the above-specified range.

[0170] As the stabilizer particles, for example, commercially available products may be used, or powder of a commercially available product may be pulverized using a known pulverizing and mixing device (such as a ball mill) before use.

[0171] In a suitable embodiment, in the raw material composition, from the viewpoint of being a reason for easily obtaining the target dental workpiece, the following method for manufacturing the dental workpiece can be cited, wherein the stabilizer (suitably Y2O3) contains a stabilizer that does not dissolve in ZrO2 and HfO2. The fact that the stabilizer contains a stabilizer that does not dissolve in zirconium oxide can be confirmed by, for example, an X-ray diffraction (XRD; X-Ray Diffraction) pattern.

[0172] When a peak derived from a stabilizer is confirmed in the XRD pattern of the raw material composition or the molded body, a stabilizer that is not solid-soluble in ZrO 2 and HfO 2 is present in the raw material composition or the molded body.

[0173] When the stabilizer is completely dissolved in ZrO2 and HfO2, the peak derived from the stabilizer is basically not confirmed in the XRD pattern. Among them, depending on the conditions such as the crystal state of the stabilizer, even if there is no peak of the stabilizer in the XRD pattern, the stabilizer is sometimes not dissolved in ZrO2 and HfO2.

[0174] Regarding the case where the stabilizer includes a stabilizer that does not form a solid solution with respect to ZrO 2 and HfO 2, an explanation is given below using yttrium trioxide as an example of the stabilizer.

[0175] In the raw material composition or the molded body of the present invention, the existence ratio of yttrium trioxide not dissolved in ZrO2 and HfO2 (hereinafter sometimes referred to as "undissolved yttrium trioxide") is y It can be calculated according to the following mathematical formula (1).

[0176] f y =I 29 / (I 28 +I 29 +I 30 )×100

[0177] (where f y Indicates the proportion of undissolved yttrium trioxide (%). In XRD measurement, I 28 The area intensity of the peak near 2θ = 28° where the main peak of the monoclinic system appears, I 29 The area intensity of the peak near 2θ = 29° where the main peak of yttrium trioxide appears, I 30 Indicates the area intensity of the peak near 2θ=30° where the main peak of the tetragonal or cubic system appears.

[0178] When a stabilizer other than yttrium trioxide is used in combination, the peak of the other stabilizer is substituted for I. 29 , which can also be used to calculate the undissolved existence rate of stabilizers other than yttrium trioxide.

[0179] From the viewpoint of easily obtaining the target dental workpiece, the existence ratio of undissolved yttrium trioxide is f y It is preferably greater than 0%, more preferably 1% or more, further preferably 2% or more, and particularly preferably 3% or more. y The upper limit of the content may be, for example, 25% or less, and is preferably determined by the content of yttrium trioxide in the raw material composition or the molded body.

[0180] For example, when the content of yttrium trioxide in the raw material composition or the molded body of the present invention is 3 mol% or more and 8 mol% or less, or when the content of yttrium trioxide is 3 mol% or more and less than 4.5 mol%, f y When the content of yttrium trioxide is 4.5 mol% or more and less than 5.8 mol%, f y When the content of yttrium trioxide is 5.8 mol% or more and 8 mol% or less, f y It can be set to 25% or less.

[0181] For example, when the content of yttrium trioxide is 3 mol% or more and less than 4.5 mol%, f y It is preferably 2% or more, more preferably 3% or more, further preferably 4% or more, and particularly preferably 5% or more.

[0182] When the content of yttrium trioxide is 4.5 mol% or more and less than 5.8 mol%, f y It is preferably 3% or more, more preferably 4% or more, further preferably 5% or more, further preferably 6% or more, and particularly preferably 7% or more.

[0183] When the content of yttrium trioxide is 5.8 mol% or more and 8 mol% or less, f y It is preferably 4% or more, more preferably 5% or more, further preferably 6% or more, further preferably 7% or more, and particularly preferably 8% or more.

[0184] In the raw material composition or molded body of the present invention, not all of the stabilizer may be solid-dissolved in ZrO2 and HfO2. It should be noted that in the present invention, the stabilizer being solid-dissolved means that, for example, the elements (atoms) contained in the stabilizer are solid-dissolved in ZrO2 and HfO2.

[0185] The Nb2O5 and / or Ta2O5 added to the raw material composition of the present invention is not particularly limited as long as the content of Nb2O5 and / or Ta2O5 contained in the dental workpiece can be adjusted to the above-mentioned specified range. Nb2O5 and / or Ta2O5 are not particularly limited, for example, commercial products can be used, and powders of commercial products can also be crushed using a known crushing and mixing device (ball mill, etc.) before use.

[0186] As a process for preparing the raw material composition, there can be listed, for example, a method of obtaining the raw material composition by wet mixing the raw materials of the aforementioned raw material composition (ZrO2, HfO2, a stabilizer, and Nb2O5 and / or Ta2O5, and a raw material compound of a Group I element (for example, a hydroxide and / or a salt of a Group I element), and further a zirconium oxide reinforcing agent as required) in a solvent containing water.

[0187] The method for wet mixing the aforementioned raw materials in a solvent containing water is not particularly limited. For example, the raw materials can be wet-mixed by using a known pulverizing and mixing device (such as a ball mill) to form a slurry, and then the slurry is dried and granulated to produce a granular raw material composition.

[0188] In the wet mixing step, additives such as a binder, a plasticizer, a dispersant, an emulsifier, a defoamer, a pH adjuster, and a lubricant may be further included. The additives may be used alone or in combination of two or more.

[0189] After adding a primary powder formed of a mixture of ZrO2, HfO2, Y2O3, and Nb2O5 and / or Ta2O5, and hydroxides and / or salts of Group I elements to water to prepare a slurry, the aforementioned binder may be subsequently added to the pulverized slurry.

[0190] The aforementioned binder is not particularly limited, and known materials can be used. Examples of the binder include polyvinyl alcohol-based binders, acrylic binders, wax-based binders (paraffin, etc.), methylcellulose, carboxymethylcellulose, polyvinyl butyral, polymethyl methacrylate, ethylcellulose, polyethylene, polypropylene, ethylene-vinyl acetate copolymers, polystyrene, atactic polypropylene, methacrylic resins, etc.

[0191] Examples of the plasticizer include polyethylene glycol, glycerin, propylene glycol, and dibutyl phthalate.

[0192] Examples of the dispersant include ammonium polycarboxylates (triammonium citrate, etc.), ammonium polyacrylates, acrylic copolymer resins, acrylate copolymers, polyacrylic acid, bentonite, carboxymethyl cellulose, anionic surfactants (e.g., polyoxyethylene alkyl ether phosphates such as polyoxyethylene lauryl ether phosphate, etc.), nonionic surfactants, olein glycerides, amine salt-type surfactants, oligosaccharide alcohols, and stearic acid.

[0193] Examples of the emulsifier include alkyl ethers, phenyl ethers, sorbitan derivatives, and ammonium salts.

[0194] Examples of the defoaming agent include alcohol, polyether, silicone, wax, and the like.

[0195] Examples of the pH adjuster include ammonia and ammonium salts (including ammonium hydroxide such as tetramethylammonium hydroxide).

[0196] Examples of the lubricant include polyoxyethylene alkyl ether and wax.

[0197] The solvent used in wet mixing is not particularly limited as long as it contains water, and an organic solvent can be used, a mixed solvent of water and an organic solvent can be used, or water alone can be used. Examples of the organic solvent include ketone solvents such as acetone and ethyl methyl ketone; alcohol solvents such as ethanol, 1-propanol, 2-propanol, 2-methyl-2-propanol, glycerol, diglycerol, polyglycerol, propylene glycol, dipropylene glycol, polypropylene glycol, ethylene glycol, diethylene glycol, polyethylene glycol, polyethylene glycol monomethyl ether, 1,2-pentanediol, 1,2-hexanediol, and 1,2-octanediol.

[0198] The raw material composition of the dental workpiece used in the present invention may contain other components in addition to ZrO2, Y2O3, Nb2O5, Ta2O5, hydroxides and / or salts of Group I elements, and zirconium oxide reinforcing agents as required, as long as the effects of the present invention are exerted. Examples of the other components include colorants (pigments and composite pigments), fluorescent agents, SiO2, etc. The other components may be used alone or in combination of two or more.

[0199] Examples of the pigment include oxides of at least one element selected from V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, Tb, and Er (specifically, NiO, Cr2O3, etc.), preferably oxides of at least one element selected from V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, and Tb, and more preferably oxides of at least one element selected from V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Sm, Eu, Gd, and Tb. However, Y2O3 and CeO2 may be excluded from the pigment.

[0200] Examples of the composite pigment include (Zr, V) O 2 , Fe(Fe, Cr) 2 O 4 , (Ni, Co, Fe)(Fe, Cr) 2 O 4 · ZrSiO 4 , and (Co, Zn) Al 2 O 4 .

[0201] Examples of the fluorescent agent include Y2SiO5:Ce, Y2SiO5:Tb, (Y,Gd,Eu)BO3, Y2O3:Eu, YAG:Ce, ZnGa2O4:Zn, BaMgAl 10 O 17 :Eu et al.

[0202] Next, the obtained raw material composition is molded to produce a molded body. The molding method is not particularly limited, and a known method (such as press molding) can be used.

[0203] When the zirconia molded body is produced by a method including the step of press-molding the raw material composition, the specific method of press-molding is not particularly limited, and a known press-molding machine can be used for the press-molding. Specific methods of press-molding include, for example, uniaxial pressing.

[0204] The pressurizing pressure is appropriately set to an optimal value according to the size of the target molded body, open porosity, biaxial bending strength, and particle size of the raw material powder, and is usually 5 MPa or more and 1000 MPa or less. By increasing the pressurizing pressure during molding in the aforementioned manufacturing method, the pores of the obtained molded body are further filled, the open porosity can be set lower, and the density of the molded body can be increased. In addition, in order to increase the density of the obtained zirconia molded body, cold isostatic pressing (CIP) treatment can also be further performed after uniaxial pressing.

[0205] Next, the obtained compact is sintered.

[0206] The term "molded body" refers to an object that has not reached a semi-sintered state (pre-fired state) or a sintered state. That is, a molded body is distinguished from a pre-fired body and a sintered body in that it is not fired after being molded into a molded body.

[0207] The sintering temperature (maximum sintering temperature) for obtaining the dental workpiece is, for example, preferably 1300°C or more, more preferably 1350°C or more, further preferably 1400°C or more, further preferably 1450°C or more, and particularly preferably 1500°C or more. In addition, the sintering temperature is, for example, preferably 1680°C or less, more preferably 1650°C or less, and further preferably 1600°C or less. As the method for producing the dental workpiece of the present invention, it is preferred that the molded body be sintered at a maximum sintering temperature of 1300 to 1680°C. The aforementioned maximum sintering temperature is preferably a temperature in the atmosphere.

[0208] From the viewpoint of being within the range of the aforementioned erosion rate (μm / g) recorded in the embodiment (A), the molded body is obtained by using a raw material composition containing a raw material compound of a Group I element. In the case of a raw material compound containing a Group I element, the holding time (retention time) at the highest sintering temperature also varies depending on the temperature, preferably less than 30 hours, more preferably less than 20 hours, more preferably less than 10 hours, more preferably less than 5 hours, particularly preferably less than 3 hours, and most preferably less than 2 hours. Furthermore, the holding time can also be set to less than 25 minutes, less than 20 minutes or less than 15 minutes. In addition, the holding time is preferably more than 1 minute, more preferably more than 5 minutes, and more preferably more than 10 minutes. According to the manufacturing method of the present invention, based on the content of the stabilizer, a dental processed body excellent in bending strength, light transmittance and machinability can be produced. In addition, as long as the effect of the present invention can be obtained, the sintering time can be shortened. By shortening the sintering time, production efficiency can be improved and energy costs can be reduced.

[0209] Regarding embodiment (B), when the molded body does not contain a raw material compound of a Group I element, from the viewpoint of being able to adjust the value of the erosion rate (μm / g)×average grain size (μm) within a specified range, the holding time (retention time) at the maximum sintering temperature can be set to 41 hours or more, 45 hours or more, and further can be set to 50 hours or more. Furthermore, the holding time can also be set to 200 hours or less, 150 hours or less, or 120 hours or less.

[0210] In the method for manufacturing a dental workpiece of the present invention, when the molded body is sintered, the heating rate is not particularly limited, but is preferably 0.1°C / min or more, more preferably 0.2°C / min or more, and further preferably 0.5°C / min or more. In addition, the heating rate is preferably 50°C / min or less, more preferably 30°C / min or less, and further preferably 20°C / min or less. By making the heating rate above the lower limit, productivity is improved.

[0211] The process of sintering the molded body can use a general dental zirconia sintering furnace. As a dental zirconia sintering furnace, a commercially available product can be used. As commercially available products, Noritake KATANA (registered trademark) F-1, F-1N, F-2 (the above are SK Medical Electronics Co., Ltd.) and the like can be listed.

[0212] Furthermore, the step of sintering the molded body preferably includes a step of performing a hot isostatic pressing (HIP) treatment in addition to the sintering at the highest sintering temperature. The HIP treatment can further improve the light transmittance and strength of the dental workpiece.

[0213] Hereinafter, the sintered body obtained by sintering at the above-mentioned maximum sintering temperature is referred to as a "primary sintered body", and the sintered body after HIP treatment is referred to as a "HIP treatment sintered body".

[0214] The HIP treatment can be performed using a known hot isostatic pressing (HIP) apparatus.

[0215] The temperature of the HIP treatment is not particularly limited. From the perspective of obtaining a high-strength and dense dental workpiece, the HIP temperature is preferably 1200° C. or higher, more preferably 1300° C. or higher, and further preferably 1400° C. or higher. In addition, the HIP temperature is preferably 1700° C. or lower, more preferably 1650° C. or lower, and further preferably 1600° C. or lower.

[0216] In the method for manufacturing a dental workpiece of the present invention, when the primary sintered body is subjected to HIP treatment, the HIP pressure is not particularly limited. From the perspective of obtaining a high-strength and dense sintered body, the HIP pressure is preferably 100 MPa or more, more preferably 125 MPa or more, and further preferably 130 MPa or more. In addition, the upper limit of the HIP pressure is not particularly limited, and can be, for example, 400 MPa or less, 300 MPa or less, and further, 200 MPa or less.

[0217] In the method for manufacturing a dental workpiece of the present invention, when the primary sintered body is subjected to HIP treatment, the heating rate is not particularly limited, but is preferably 0.1°C / min or more, more preferably 0.2°C / min or more, and further preferably 0.5°C / min or more. In addition, the heating rate is preferably 50°C / min or less, more preferably 30°C / min or less, and further preferably 20°C / min or less. By making the heating rate above the lower limit, productivity is improved.

[0218] In the method for manufacturing a dental workpiece of the present invention, when the primary sintered body is subjected to HIP treatment, the HIP time is not particularly limited. From the perspective of obtaining a high-strength and dense dental workpiece, the HIP treatment time is preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 30 minutes or more. In addition, the HIP treatment time is preferably 10 hours or less, more preferably 6 hours or less, and even more preferably 3 hours or less.

[0219] In the method for manufacturing a dental workpiece of the present invention, when the aforementioned primary sintered body is subjected to HIP treatment, the pressure medium is not particularly limited. From the viewpoint of low impact on zirconium oxide, the pressure medium can be selected from at least one of oxygen, oxygen containing 3% hydrogen, air and inert gas (such as nitrogen, argon, etc.).

[0220] When the primary sintered body is subjected to the HIP treatment in an oxygen mixed gas atmosphere, the oxygen concentration is not particularly limited, and may be, for example, more than 0% and not more than 20%.

[0221] When the oxygen mixed gas is used, as a gas other than oxygen, at least one inert gas (for example, nitrogen gas, argon gas, etc.) can be selected.

[0222] In the manufacturing method of the dental workpiece of the present invention, during the aforementioned HIP treatment, if an inert gas or the like is used in a reducing atmosphere, blackening may sometimes occur due to oxygen defects. In this case, in order to remove the blackening, after the aforementioned HIP treatment step, it is preferably included: a step of heat treatment at a temperature below 1650°C and in the air or in an atmosphere with an excess of oxygen (hereinafter also referred to as "tempering treatment"), and from the viewpoint of effectively performing the heat treatment, it is more preferably performed in an atmosphere with an excess of oxygen. An atmosphere with an excess of oxygen refers to an atmosphere in which the oxygen concentration is greater than that in the air. As an atmosphere with an excess of oxygen, there is no particular limitation as long as the oxygen concentration exceeds 21% and is below 100%, and it can be appropriately selected from this range. For example, the oxygen concentration can be set to 100%.

[0223] The dental workpiece of the present invention is not particularly limited as long as the effects of the present invention are exhibited, and may be a primary sintered body, a HIP-treated sintered body, or a tempered sintered body.

[0224] As a preferred embodiment, there is a dental workpiece which is a sintered body after tempering.

[0225] The heat treatment temperature in the air or in an oxygen-excess atmosphere may be appropriately changed according to the aesthetics of the dental workpiece (for example, the color of a dental prosthesis).

[0226] In a preferred embodiment, from the viewpoint of the aesthetics of the dental workpiece, the heat treatment temperature in air or in an oxygen-excess atmosphere is preferably 1650° C. or lower, more preferably 1600° C. or lower, and further preferably 1550° C. or lower.

[0227] In other preferred embodiments, from the viewpoint of the aesthetics of the dental workpiece, the heat treatment temperature in air or in an oxygen-excess atmosphere is preferably 1400° C. or lower, more preferably 1300° C. or lower, and even more preferably 1200° C. or lower.

[0228] Furthermore, in any embodiment, the temperature of the heat treatment is preferably 500° C. or higher, more preferably 600° C. or higher, and even more preferably 700° C. or higher.

[0229] The above-mentioned tempering treatment can use a general dental zirconia firing furnace. As a dental zirconia firing furnace, a commercially available product can be used. As commercially available products, Noritake KATANA (registered trademark) F-1, F-1N, F-2 (the above are SK Medical Electronics Co., Ltd.) and the like can be listed.

[0230] The dental workpiece of the present invention has excellent machinability despite being a sintered body, and therefore, it is not necessary to machine a semi-sintered calcined body in a ground state and then sinter it to obtain a sintered body.

[0231] On the other hand, as a method for producing a dental workpiece, a method may be adopted in which a molded body obtained using the raw material composition is pre-fired to produce a semi-sintered pre-fired body, and the unprocessed pre-fired body is machined to produce a sintered body.

[0232] In the case where the dental workpiece is a sintered body containing zirconium oxide, as another embodiment, the following method for manufacturing a dental workpiece can be listed, which includes: a step of preparing a molded body using the aforementioned raw material composition; a step of pre-calcining the obtained molded body to obtain a zirconium oxide calcined body (pre-calcining step); and a step of sintering the zirconium oxide calcined body.

[0233] In order to reliably perform agglomeration, the firing temperature (pre-firing temperature) in the pre-firing step is, for example, preferably 800° C. or higher, more preferably 900° C. or higher, and further preferably 950° C. or higher.

[0234] The calcining temperature is preferably, for example, 1200° C. or less, more preferably 1150° C. or less, and further preferably 1100° C. or less. The calcining temperature is preferably, for example, 800° C. to 1200° C. It is believed that at such a calcining temperature, the stabilizer will not be dissolved significantly during the calcining step.

[0235] The calcined zirconium oxide body of the present invention refers to a body in which ZrO2 particles are necked (fixed) to each other and the ZrO2 particles (powder) are not completely sintered (semi-sintered state).

[0236] The density of the calcined zirconium oxide is preferably 2.7 g / cm 3 In addition, the density of the zirconia calcined body is preferably 4.0 g / cm 3 Below, more preferably 3.8 g / cm 3 Below, more preferably 3.6 g / cm 3 When the density is within this range, processing can be easily performed. The density of the calcined body can be calculated, for example, in the form of (mass of the calcined body) / (volume of the calcined body).

[0237] The three-point bending strength of the calcined zirconium oxide body is preferably 15 to 70 MPa, more preferably 18 to 60 MPa, and even more preferably 20 to 50 MPa.

[0238] The bending strength can be measured using a test piece of 5 mm thickness × 10 mm width × 50 mm length, in accordance with ISO6872:2015 except for the size of the test piece. The surface of the test piece and the C surface (the surface obtained by chamfering the corner of the test piece at an angle of 45°) are surface-finished along the length direction using 600 sandpaper. The test piece is configured in a manner such that the widest surface faces the vertical direction (load direction). In the bending test measurement, the span is set to 30 mm and the slider speed is set to 1.0 mm / min.

[0239] The step of sintering the zirconia calcined body can be performed using the same method and conditions (temperature, pressure, etc.) as the step of sintering the molded body. Therefore, in the embodiment of the manufacturing method using the zirconia calcined body, the "molded body" can also be understood as the "calcined body".

[0240] The dental workpiece of the present invention has excellent strength. The biaxial bending strength of the dental workpiece of the present invention is preferably 300 MPa or more, more preferably 350 MPa or more, further preferably 400 MPa or more, further preferably 450 MPa or more, and particularly preferably 500 MPa or more. By making the dental workpiece of the present invention have such biaxial bending strength, when used as, for example, a dental prosthesis, breakage in the oral cavity can be suppressed. The upper limit of the biaxial bending strength is not particularly limited, and the biaxial bending strength can be, for example, set to 1200 MPa or less, and further can be set to 1000 MPa or less.

[0241] In addition, the biaxial bending strength of the dental workpiece can be measured in accordance with ISO6872:2015.

[0242] The dental workpiece of the present invention preferably has high light transmittance. Light transmittance can be evaluated using ΔL*. Regarding light transmittance, specifically, the ΔL* of the dental workpiece of the present invention when the diameter is 15 mm and the thickness is 1.2 mm is preferably 10 or more, more preferably 12 or more, further preferably 13 or more, and particularly preferably 14 or more. By making this ΔL* within the above range, a dental workpiece with high light transmittance can be obtained.

[0243] ΔL* refers to the difference between the lightness of the same sample under a white background (first L* value) and the lightness under a black background (second L* value). Specifically, it refers to the difference between the L* value under a white background (JIS Z8781-4:2013 Color Measurement - Part 4: CIE 1976 L*a*b* Color Space) and the L* value under a black background. The white background refers to the white part of the obscuration test paper recorded in Section 1 of Part 4 of JIS K 5600-4-1:1999, and the black background refers to the black part of the aforementioned obscuration test paper.

[0244] The upper limit of ΔL* is not particularly limited, but is, for example, 25 or less, and can be further 20 or less from the viewpoint of aesthetics.

[0245] It should be noted that ΔL* of the dental workpiece when the diameter is 15 mm and the thickness is 1.2 mm can be measured using a spectrophotometer, for example, a dental colorimetric device ("Crystaleye CE100-CE / JP", 7-band LED light source, analysis software "Crystaleye" (manufactured by Olympus Corporation)).

[0246] As dental prostheses manufactured using the dental processed body of the present invention, for example, in addition to dental crown restorations such as inlays, onlays, veneers, crowns, core-integrated crowns, and bridges, abutment teeth, dental posts, dentures, denture gums, implant components (fixtures, abutments), etc. can also be listed. In addition, machining is preferably performed using, for example, a commercially available dental CAD / CAM system. As examples of the CAD / CAM system, the CEREC system manufactured by Dentsply Sirona and the "KATANA (registered trademark) system" manufactured by KurarayNoritake Dental can be listed.

[0247] Furthermore, the dental workpiece of the present invention can be used for purposes other than dental purposes, and is particularly suitable for use in zirconia components that require an irregular or complex shape and strength.

[0248] The dental workpiece of the present invention can be processed directly on a sintered body without using existing manufacturing methods (injection molding, CIP, casting molding, or 3D printing, etc.). Therefore, it is economical when, for example, a desired zirconia component can be obtained in a short time, and in the case of a complex-shaped component that is difficult to manufacture using a conventional manufacturing method, it is not necessary to obtain multiple components by mechanical interlocking, so a zirconia component that maintains high strength can be obtained.

[0249] Furthermore, the sintered body can be processed directly, so when dimensional accuracy is required, a sintering step is not required, and there is no uneven sintering shrinkage, so a zirconia component can be obtained with high accuracy. Specifically, it can also be used as a method for manufacturing jewelry accessories, engine components and interior components of mobile bodies such as aircraft and automobiles, frame materials for display panels, building components, electrical product components, household product components, and toy components.

[0250] Furthermore, the present zirconia component may be used as a composite component by fitting it with a different material.

[0251] The present invention includes various embodiments in which all or part of the above-mentioned configurations are combined within the scope of the technical concept of the present invention as long as the effects of the present invention are exhibited.

[0252] Example

[0253] The following examples are given to more specifically illustrate the present invention, but the present invention is not limited to these examples at all, and a person with common knowledge in the art can make various changes within the scope of the technical concept of the present invention. It should be noted that in the following examples and comparative examples, the average particle size refers to the average primary particle size, which can be obtained by a laser diffraction scattering method. Specifically, a laser diffraction particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation) can be used to measure 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium and on a volume basis.

[0254] [Examples 1 to 8 and Comparative Example 1]

[0255] The measurement samples of the respective Examples and Comparative Examples were produced through the steps of producing a granular raw material composition, producing a molded body, and producing a sintered body (producing a primary sintered body, HIP treatment, and tempering treatment).

[0256] [Preparation of Granular Raw Material Composition]

[0257] In order to prepare the granular raw material composition of each embodiment and comparative example, commercially available ZrO2 powder, Al2O3 powder, Y2O3 powder, Nb2O5 powder, TiO2 powder, hydroxide or carbonate of the first group element are mixed in a manner showing the composition described in Table 1 and Table 2, water is added to prepare a slurry, and wet pulverization and mixing are performed using a ball mill until the average particle size reaches 0.13μm or less. After adding a binder to the pulverized slurry, it is dried using a spray dryer to prepare a granular raw material composition (hereinafter also referred to as "raw material composition") for the manufacture of the molded body described later. The above average particle size is a value obtained by using a laser diffraction particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation) using a 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium and measuring on a volume basis.

[0258] [Production of Molded Body]

[0259] In order to obtain sintered body samples for evaluation of light transmittance and strength and evaluation of processability in each of the Examples and Comparative Examples, a pellet-shaped molded body and a block-shaped molded body were produced as follows.

[0260] The pellet-shaped molded body was prepared by using a cylindrical mold having a diameter of 19 mm, and the raw material composition was placed in the mold so that the thickness of the dental workpiece after sintering would be 1.2 mm.

[0261] Next, the raw material composition was press-molded at a surface pressure of 200 MPa using a uniaxial press molding machine to produce a pellet-shaped molded body.

[0262] In addition, regarding the block-shaped molded body, the raw material composition was placed in a mold having an inner size of 19 mm×18 mm so that the height of the dental workpiece after sintering would be 14.5 mm.

[0263] Next, the raw material composition was press-molded at a surface pressure of 200 MPa using a uniaxial press molding machine to produce a block-shaped molded body.

[0264] [Production of primary sintered body]

[0265] For the obtained pellet-shaped and block-shaped molded bodies, the sintering furnace "Noritake KATANA (registered trademark) F-1" manufactured by SK Medical Electronics Co., Ltd. is used to retain them in the atmosphere at the maximum sintering temperature listed in Tables 1 and 2 for 2 hours, thereby obtaining pellet-shaped and block-shaped samples of sintered bodies containing zirconium oxide or sintered bodies containing aluminum oxide (primary sintered bodies).

[0266] In addition, in Example 6 below, the HIP treatment and the tempering treatment were not performed, and the primary sintered body was used as a dental workpiece to evaluate various properties.

[0267] [Production of HIP-treated sintered body]

[0268] The obtained pellet-shaped and block-shaped sintered body containing zirconium oxide or the sintered body containing aluminum oxide (primary sintered body) was retained at 150 MPa for 2 hours at the HIP temperature described in Tables 1 and 2 using a HIP device "O2-Dr.HIP" manufactured by Kobe Steel, Ltd., to obtain samples of a pellet-shaped and block-shaped sintered body containing zirconium oxide or the sintered body containing aluminum oxide (HIP-treated sintered body).

[0269] [Production of dental workpiece (sintered body after tempering)]

[0270] The obtained pellet-shaped and block-shaped sintered bodies containing zirconium oxide or alumina (HIP-treated sintered bodies) were retained at 700°C for 60 hours using a sintering furnace "Noritake KATANA (registered trademark) F-1" manufactured by SK Medical Electronics Co., Ltd., thereby obtaining pellet-shaped and block-shaped dental workpieces (tempered sintered bodies) samples. The size of the obtained samples was 15 mm in diameter × 1.2 mm in thickness for the pellet shape, and 15.7 mm in width × 16.5 mm in length × 14.5 mm in height for the block shape.

[0271] It should be noted that the content of each component of the sintered body in Table 1 and Table 2 is a value calculated from the charge amount of the raw material.

[0272] The contents (mol %) of the Group I elements in Tables 1 and 2 are external addition rates relative to 100 mol % of the total of ZrO 2 , HfO 2 , the aforementioned stabilizers, Nb 2 O 5 , and Ta 2 O 5 .

[0273] The contents (mol%) of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5, and Ta2O5 in Tables 1 and 2 are the contents of each component in the total of 100 mol% of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5, and Ta2O5. For only ZrO2 and HfO2, the total contents of ZrO2 and HfO2 are expressed as total contents of ZrO2 and HfO2.

[0274] The content (mass %) of TiO 2 in Tables 1 and 2 is an external addition rate relative to 100 mass % of the total of ZrO 2 , HfO 2 , the aforementioned stabilizer, Nb 2 O 5 , and Ta 2 O 5 .

[0275] A / B in Tables 1 and 2 represents the ratio of A to B when the content of Y2O3 is Amol% and the total content of Nb2O5 and Ta2O5 is Bmol%.

[0276] The dental workpieces obtained in the respective Examples and Comparative Examples were evaluated for their properties by the following methods. The obtained results are shown in Tables 1 and 2 below.

[0277] [MSE test]

[0278] For each sample of the workable zirconia composite sintered body of the Examples and Comparative Examples, one sample (width 15.7 mm×length 16.5 mm×height 3.0 mm) was prepared and evaluated using a slurry local jet abrasion apparatus (MSR-A model, manufactured by Palmeso).

[0279] In the evaluation, 3 volume % of spherical alumina (model: MSE-BA-3-3, manufactured by Palmeso) having an average particle size of 3.0 μm was mixed into water to prepare spherical alumina slurry, which was then used in the slurry local jet abrasion method. The produced spherical alumina slurry was used immediately after production.

[0280] Regarding the projection pressure, the obtained spherical alumina slurry was projected onto a standard test piece (model: HRC45, manufactured by Palmeso), and the projection pressure was adjusted so that a reference value (erosion rate: 1.00 μm / g±5%) appeared.

[0281] As the projection conditions during evaluation, an impact mode was selected in which the gas pressure supplied to the projection nozzle was set to 0.335 MPa, the slurry pressure was set to 0.317 MPa, the gas flow rate supplied to the projection nozzle was set to 10.8 L / min, and the slurry flow rate was set to 125 L / min.

[0282] The projection force in the impact mode was confirmed by the erosion rate of 24.0±5% μm / g on a standard test piece made of acrylic resin.

[0283] [Measurement of wear depth and calculation of erosion rate caused by wear]

[0284] The slurry local spray abrasion method was performed using spherical alumina slurry containing spherical alumina particles by slurry spraying. Three measurement locations were randomly selected for one sample under the following measurement conditions. The wear depth (erosion depth) of the sample was measured for each measurement location.

[0285] Next, the maximum value D (μm) of the wear depth is measured respectively based on the obtained profile. Next, based on the relationship pre-set for the spherical alumina slurry containing spherical alumina particles, the amount of projected particles (g) projected on the sample is calculated based on the slurry flow rate supplied to the projection nozzle 50. And, for the sample, the average value of the maximum value D (μm) is divided by the amount of projected particles (g), thereby calculating the spherical particle wear rate (spherical particle erosion rate) (μm / g) when the slurry local jet abrasion method using the spherical alumina slurry containing spherical alumina particles is adopted. The average values ​​of the erosion rates of the above-mentioned three measurement locations are shown in Tables 1 and 2.

[0286] (Measurement conditions)

[0287] Model used: Stylus type measuring instrument (PU-EU1) manufactured by Kosaka Laboratory Co., Ltd.

[0288] Stylus load: 100μN

[0289] Measurement magnification: 10000

[0290] Side length: 4mm

[0291] Measuring speed: 0.2mm / sec

[0292] [Evaluation of light transmittance of dental workpieces]

[0293] The pellet-shaped dental workpiece (sintered body after tempering) of each example and comparative example was used as it is (diameter about 15 mm × thickness 1.2 mm), and the light transmittance was evaluated by the following method (n=3). As a measuring device, a dental colorimetric device "Crystaleye" (7-band LED light source) manufactured by Olympus was used. First, the background (backing plate) of the sample was set to white (the side opposite to the measuring device relative to the sample was set to white), and the L* value of the L*a*b* colorimetric system (JIS Z 8781-4:2013 Colorimetry-Part 4: CIE 1976 L*a*b* color space) was measured, and it was set as the first L* value. Next, for the same sample after the first L* value was measured, the background (backing plate) of the sample was set to black (the side opposite to the measuring device relative to the sample was set to black), and the L* value of the L*a*b* colorimetric system was measured, and it was set as the second L* value.

[0294] In the present invention, the difference between the first L* value and the second L* value (the value obtained by subtracting the second L* value from the first L* value) is set as light transmittance, expressed as ΔL*. The higher the ΔL*, the higher the light transmittance, and the lower the ΔL*, the lower the light transmittance. When measuring the chromaticity, the black and white colors used as the background (pad) can use the obscuration test paper used in the relevant measurement of the coating described in JIS K 5600-4-1:1999. The average value of ΔL* of each sample is shown in Tables 1 and 2 as the result.

[0295] In the embodiment where light transmittance is required, a ΔL* of 10 or more is considered acceptable.

[0296] [Strength evaluation of dental workpieces]

[0297] The samples of the pellet-shaped dental workpieces (sintered bodies after tempering) of the embodiments and comparative examples were used as they are, and the universal testing machine "AGS-X" (manufactured by Shimadzu Corporation) was used, and the slide speed was set to 1.0 mm / min, and the biaxial bending strength (n=5) was measured in accordance with ISO6872:2015. The average values ​​are shown in Tables 1 and 2 as the measurement results. As for the strength, 300 MPa or more was considered acceptable.

[0298] [Method for measuring average grain size in sintered body]

[0299] In the pellet-shaped dental workpiece (sintered body after tempering) of each example and comparative example, a scanning electron microscope (trade name "VE-9800", manufactured by Keyence Corporation) was used to obtain a surface image. After recording the grain boundaries of each crystal grain in the obtained image, the average grain size was calculated by image analysis.

[0300] In the measurement of the average grain size, image analysis software (trade name "Image-Pro Plus", manufactured by Bodong Co., Ltd.) is used to binarize the read SEM image, adjust the brightness range so that the grain boundary is clear, and identify the particles from the field of view (area). The grain size obtained by using Image-Pro Plus refers to: for the length of the line segment obtained by connecting the outline lines passing through the center of gravity obtained by the outline lines of the crystal particles, the grain size obtained by measuring and averaging with the center of gravity as the center and at a scale of 2 degrees, in the SEM photo images (3 fields of view) of each embodiment and comparative example, the average value of the grain size of all particles not involving the end of the image is set as the average grain size (number basis) in the sintered body.

[0301] "Particles not involving the image ends" refers to particles that do not completely fall within the SEM image (particles whose outlines are cut off at the upper, lower, left, and right boundaries). The grain size of all particles not involving the image ends is selected in Image-Pro Plus by selecting the option to remove all particles on the boundary lines.

[0302] [Evaluation of processability of dental workpieces]

[0303] For the block-shaped dental workpiece (sintered body after tempering) samples of each embodiment and comparative example, 30 samples with metal fixtures bonded on the surface of about 15.7 mm in width and 14.5 mm in height were prepared, and processed into the crown shape of a general front tooth using the CEREC system "MC-XL" (manufactured by Dentsply Sirona). The processing program used the software "inLab (registered trademark) CAM virsion 20.0.1.203841", the manufacturer selected was IVOCLAR VIVADENT, the material name selected was IPS e.max CAD, the production method selected was grinding, the block size selected was C16, and the processing tools used were Step Bur12 and CylinderPointedBur 12S.

[0304] [Processing time]

[0305] The machining time shown in Tables 1 and 2 refers to the time required to complete machining of the first sample from the start of machining of the sample using a new machining tool under the conditions described in the above-mentioned [Evaluation of Machinability of Dental Workpiece].

[0306] In addition, if an error occurs due to the load during processing, etc., and the CEREC system "MC-XL" stops during processing, a new processing tool is replaced and installed, and processing is restarted. This operation is repeated until the processing of one sample is completed, and the required time is set as the processing time.

[0307] [Number of pieces processed]

[0308] The number of samples processed shown in Tables 1 and 2 refers to the number of samples that can be processed into the crown shape of incisors without changing the processing tools at all, starting the processing of the samples using a new set of processing tools under the conditions described in the above [Evaluation of the processability of dental workpieces]. The maximum number of samples used in the test was 30, and when processing could be completed with one processing tool up to 30 samples, no additional processing test was performed, and it was always set as "30 or more".

[0309] In addition, before the processing of the first sample is completed, an error occurs due to the load during processing, etc., and when the MC-XL stops during processing, a new processing tool is replaced and installed, and processing is restarted. This operation is repeated until the processing of one sample is completed, and the reciprocal of the number of processing tools used is set as the number of processing. For example, "0.2" in Comparative Example 1 in Table 2 means that using 5 processing tools, a sample processed into the shape of a crown of an incisor can be obtained.

[0310] surface

[0311] [Table 2]

[0312]

[0313] From the above results, it was confirmed that the dental workpiece of the present invention has strength and light transmittance suitable for dental use and is excellent in machinability in a sintered state.

[0314] In addition, in Examples 1 to 3, the consumption of the processing tool can be suppressed, and the number of dental prostheses that can be continuously processed by one processing tool can be increased compared to the conventional art.

[0315] Furthermore, it was confirmed that the dental workpiece of the present invention has strength and light transmittance suitable for dental use even in an embodiment requiring high light transmittance, and has excellent machinability in a sintered state.

[0316] On the other hand, in Comparative Example 1, which is equivalent to Patent Document 1 and in which the erosion rate does not fall within the prescribed range, the reduction in machining time is insufficient.

[0317] Industrial Applicability

[0318] The dental workpiece of the present invention has suitable strength and light transmittance and is excellent in machinability, and is particularly useful as a dental material such as a dental prosthesis for dental treatment.

[0319] Description of Reference Numerals

[0320] 10: Slurry local injection abrasion device

[0321] 34: Slurry

[0322] 35: Slurry tank

[0323] 36: Blender

[0324] 38: Compressed air source

[0325] 40: Slurry pressure regulating valve

[0326] 42: Sling gun

[0327] 44: Slurry flow meter

[0328] 46: Gas pressure regulating valve

[0329] 48: Gas flow meter

[0330] 50: Projection nozzle

[0331] 52: Fixture

[0332] 54: Projection Container

[0333] 56: Base drive device

[0334] 58: Recovery pump

Claims

1. A dental workpiece, wherein: In the microparticle spraying test, when a spherical alumina slurry with an average particle size of 3.0 μm is projected, the erosion rate is 6.5 μm / g or more, or the value of the erosion rate (μm / g) × average grain size (μm) is 15 μm. 2 / g or above, The biaxial bending strength measured according to ISO6872:2015 is 300 MPa or more.

2. The dental workpiece according to claim 1, wherein: In the microparticle spraying test, when spherical alumina slurry with an average particle size of 3.0 μm was projected, the erosion rate was 8.0 μm / g or more.

3. The dental workpiece according to claim 1 or 2, wherein: The dental workpiece is a ceramic sintered body.

4. The dental workpiece according to claim 3, wherein: The ceramic sintered body is a sintered body containing zirconium oxide.

5. The dental workpiece according to any one of claims 1 to 4, wherein The average grain size of the dental workpiece is 0.05 to 15.0 μm.

6. The dental workpiece according to any one of claims 1 to 5, wherein In the microparticle spraying test, when a spherical alumina slurry with an average particle size of 3.0 μm is projected, the value of erosion rate (μm / g) × average grain size (μm) is 15 μm. 2 / g or above.

7. The dental workpiece according to claim 5, wherein: In the microparticle spraying test, when a spherical alumina slurry with an average particle size of 3.0 μm is projected, the value of erosion rate (μm / g) × average grain size (μm) is 15 μm. 2 / g or more, and the average grain size of the dental workpiece is 3.0 μm to 15.0 μm.

8. The dental workpiece according to claim 5, wherein: In a fine particle spraying test, the erosion rate when projecting spherical alumina slurry having an average particle size of 3.0 μm was 8.0 μm / g or more, and the average grain size of the dental workpiece was 0.05 μm to 5.0 μm.

Citation Information

Patent Citations

  • Cheap machinable zirconium oxide ceramic dental repairing body and preparation thereof

    CN1489988A

  • Production method for workable zirconia composite sintered body, raw material composition for workable zirconia composite sintered body, and workable zirconia composite calcined body

    WO2021132644A1